Fault diagnosis and fault-tolerant control of robotic and autonomous systems - Monteriù, Andrea; Longhi, S.; Freddi, Alessandro (IET control, robotics and sensors series, 2020)
This book covers: fault diagnosis, fault tolerant control, unmanned aerial vehicles, quadrotors, observer based control, service robots, nonlinear optimal control, robot manipulators, and industrial robotic systems.